PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, AGENCY COST DAN SALES GROWTH TERHADAP KEMUNGKINAN TERJADINYA FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2015) - Dwi Rafika Rani; Hardi Hardi; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to examine the influence of liquidity, leverage, profitability, agency cost, and sales growth on probability of financial distress.The population in this study consists of all manufacturing company in Indonesia Stock Exchange in year 2013-2015. Sampling method used is purposive sampling. A criterion for firm with probability of financial distress is a company which is has a negative earning per share in a year ended. Data of these listed companies one and two years before they selected as samples. By omitting companies with some data unavailable, the samples consist of 94 companies. Logistic regression used to be analysis technique. The empirical result of this study show that only leverage has a negative significant influence to prabibility of financial distress. Liquidity, profitability, agency cost and sales growth have no influence to prabibility of financial distress.Keywords : Liquidity, Leverage, Profitability, Agency Cost, Sales Growth, Financial Distress .